Causal Relationship Between Psoriasis and Bullous Pemphigoid: A Mendelian Randomization Analysis - Xiaoxue Wang; Zexin Zhu (Dermatology Practical & Conceptual)
Introduction: Psoriasis and bullous pemphigoid (BP) are the 2 major types of immune-mediated inflammatory skin diseases. Studies have reported the association between psoriasis and BP; however, no studies reported whether a causal relationship exists between these 2 skin diseases.